Comparing sterofundin to 0.9% sodium chloride infusion in managing diabetic ketoacidosis: a pilot study - Rossman H; Mahathar AW; Nik Azlan Nik Muhamad (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Fluid replacement is the mainstay treatment for diabetic ketoacidosis (DKA). Currently, the best choice of fluids is still debatable. An amount of 0.9% sodium chloride is commonly used. Sterofundin® is an alternative crystalloid that is assumed to expedite resolution of acidosis. Advantages in sterofundin content being smaller significant ion difference (SID) to plasma and lower chloride content. The main objective of the study was to compare rate of acidosis resolution in DKA patients between treatment with 0.9% normal saline and Sterofundin over 12 hrs. Other objectives were to compare significant ion difference (SID), 12-hr blood ketone clearance and electrolyte balance between the two groups. The study was a prospective open labelled randomized control trial. This study was conducted over 6 months. Sample size of 18 was obtained with 9 for each arm. Main difference between two groups was initial median 2-hr pH level improvement (NS = +0.006 vs. Sterofundin = +0.05, P=0.063), however not being significant. Ketone, anion gap reduction, bicarbonate normalisation, sodium, chloride, urea and creatinine levels failed to show any significant differences between both groups. Twelve-hour median chloride levels increments were higher in the NS group (+11) compared to the sterofundin group (+6). There was no difference between mortality and morbidity. Comparing the two fluid groups, there was no significant biochemical differences during treatment of DKA. This was a pilot study that can initiate further clinical trials.